2019
DOI: 10.1186/s12917-019-2133-0
|View full text |Cite
|
Sign up to set email alerts
|

No evidence of avian influenza antibodies in two species of raptor nestlings inhabiting Norway

Abstract: BackgroundSince 2016, incursions of highly pathogenic avian influenza virus (HPAIV) H5N8 clade 2.3.4.4b have caused unprecedented clinical signs and mortality in white-tailed eagles (WTE; Haliaeetus albicilla) across Europe and have been found to be infecting other raptor species, such as the northern goshawk (NG; Accipiter gentilis). Before this study, no screening of Norwegian raptors had been undertaken.ResultsPlasma samples from 43 white-tailed eagle and 29 northern goshawk nestlings, from several location… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Wild raptors also have been affected by severe HPAI disease during earlier HPAIV epizootics 7 12 , 15 . Studies on those birds showed that HPAI viruses in wild raptors are primarily neurotropic, and that infected raptors usually present with neurologic signs due to encephalitis, often resulting in death 8 , 10 , 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Wild raptors also have been affected by severe HPAI disease during earlier HPAIV epizootics 7 12 , 15 . Studies on those birds showed that HPAI viruses in wild raptors are primarily neurotropic, and that infected raptors usually present with neurologic signs due to encephalitis, often resulting in death 8 , 10 , 15 .…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the virological HPAIV testing, few studies have focused on serum antibody analysis. Previous studies failed to detect AIV-reactive antibodies in raptor nestlings during similar sampling approaches in Northern Europe (Gunnarsson et al, 2010; Lee et al, 2019). Here, we analysed raptor sera on a larger scale and detected antibodies against IVA NP (n=8; in 2017, 2021 and 2022) and H5 (n=1; in 2022) exclusively in WTSE nestlings.…”
Section: Discussionmentioning
confidence: 89%
“…Conceivably, HPAIV H5 infection in immunologically naïve avian raptor species has been shown to induce severe and often fatal disease. These findings have prompted investigations of using avian raptors as indicator species to monitor geographical expansion of HPAIV activity in general and incursion events of HPAIV H5 into new regions, as recently described for the transatlantic spread of HPAIV H5, clade 2.3.4.4b, via Iceland (Günther et al, 2022; Lee et al, 2019).…”
Section: Discussionmentioning
confidence: 97%
“…IAVs have been detected in multiple wildlife species in Arctic regions, including seabirds, shorebirds, waterfowl, seals, sea lions, whales, and terrestrial mammals, and in the environment [ 11 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ]. IAV genomic sequence data are available through multiple publicly accessible databases (i.e., GenBank, NCBI, IVR, GISAID); however, many published sequences from countries with territory in Arctic regions lack specific sampling location data, making it difficult to identify sequences isolated specifically from these regions.…”
Section: Resultsmentioning
confidence: 99%